Genes in the High-Density Lipoprotein Metabolic Pathway in Age-related Macular Degeneration and Polypoidal Choroidal Vasculopathy - Liu, Ke; Chen, Li Jia; Lai, Timothy Y.Y.; Tam, Pancy O.S.; Ho, Mary; Chiang, Sylvia W.Y.; Liu, David T.L.; Young, Alvin L.; Yang, Zhenglin; Pang, Chi Pui (Ophthalmology (Rochester, Minn.), 2014)
To investigate the associations of genetic variants in the high-density lipoprotein (HDL) metabolism pathway with neovascular age-related macular degeneration (AMD) and polypoidal choroidal vasculopathy (PCV). Cross-sectional, case-control association study. A Chinese case-control group of 200 neovascular AMD patients, 233 PCV patients, and 275 control subjects. Eight single nucleotide polymorphisms (SNPs) from 6 genes of the HDL metabolism pathway and 2 known AMD-associated SNPs, rs800292 (from complement factor H [CFH]) and rs11200638 (from HtrA serine peptidase 1 [HTRA1]), were genotyped in all study subjects using the TaqMan genotyping technology (Applied Biosystems, Foster City, CA). Allele and genotypic frequencies of selected SNPs. The SNP rs3764261 in the cholesteryl ester transfer protein (CETP) gene was associated significantly with neovascular AMD (P = 1.82×10−4; odds ratio [OR], 1.89) and PCV (P = 4.04×10−4; OR, 1.80). The associations remained significant after adjusting for the CFH SNP rs800292 and the HTRA1 SNP rs11200638. A significant interaction between the CETP SNP rs3764261 and the CFH SNP rs800292 existed in both neovascular AMD and PCV, the rs800292 G allele conferring a significantly increased risk of the diseases only in individuals carrying the risk allele T of rs3764261. A borderline association was detected between the ATP-binding cassette, subfamily G, member 1 (ABCG1) gene SNP rs57137919 and PCV (P = 0.03). Our results showed that CETP is a susceptibility gene for neovascular AMD and PCV and that ABCG1 a putative gene for PCV. CETP exerts a modifying effect on CFH in the genetic risk. Our data suggest a link of the HDL metabolism pathway with neovascular AMD and PCV.